2016
DOI: 10.7567/apex.9.042601
|View full text |Cite
|
Sign up to set email alerts
|

Fast and high light yield scintillation in the Ga2O3 semiconductor material

Abstract: We report the distinct scintillation properties of the well-known Ga2O3 semiconductor material. Under UV excitation, the photoluminescence (PL) emission peak appeared near a wavelength of 380 nm with a quantum yield of 6%, and fast decays of 8 and 793 ns were observed. In contrast, the X-ray-induced scintillation spectrum showed an intense emission band near a wavelength of 380 nm, whose decay curve was reproduced using two exponential decay components with time constants of 8 and 977 ns. The pulse height spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 37 publications
2
30
1
Order By: Relevance
“…The emission profile under ultraviolet excitation and X-ray excitation was basically the same, concluding the existence of similar decay channels. Yanagida and coworkers [81] report the scintillation properties of β-Ga2O3 as shown in Figure 7b,d. The emission band is mainly composed of two peaks in the UV and blue ranges.…”
Section: Emission Decay Dynamics In Oxides 321 Binary Oxidesmentioning
confidence: 92%
“…The emission profile under ultraviolet excitation and X-ray excitation was basically the same, concluding the existence of similar decay channels. Yanagida and coworkers [81] report the scintillation properties of β-Ga2O3 as shown in Figure 7b,d. The emission band is mainly composed of two peaks in the UV and blue ranges.…”
Section: Emission Decay Dynamics In Oxides 321 Binary Oxidesmentioning
confidence: 92%
“…CsPbBr 3 nanocrystal scintillators demonstrated a short decay time of 44.6 ns under gamma excitation. 38 The same material displayed a 5 ns decay time upon UV excitation, with the faster decay potentially due to avoiding the additional excitation and cascade steps in RL, 79 combined with the shorter penetration depth of UV compared to X-rays exciting the surface. The decay time shortened to 3 ns once combined in a Cs 4 PbBr 6 matrix, attributed to additional confinement accelerating recombination.…”
Section: Pvk Scintillator Performancementioning
confidence: 99%
“…It has been reported that the decay time measured from RL excitation is slower, due to the additional excitation and cascade steps. 79 …”
Section: General Scintillator Considerationsmentioning
confidence: 99%
“…44) Scintillation due to free exciton is characterized by fast scintillation decay with a sharp emission peak in the spectrum. Recently, I found a newly developed semiconductor material, Ga 2 O 3 , which also shows fast and very intense scintillation upon γ-ray irradiation, 45) although it is under discussion whether the emission is like that of a direct transition semiconductor or not. Among the semiconductor scintillators developed so far, Ga 2 O 3 has been confirmed to show the highest scintillation light yield, and we continue to study this scintillator.…”
Section: Recent Randd Progress Of Scintillatorsmentioning
confidence: 99%